Germans of Turkestan: Formation of an Ethnic Community from 1880s to 1906 - V. N. Shaidurov; S. N. Navruzov; U. M. Abdalov (Научный диалог)
This study examines the migration and demographic development of German landowner settlers in the Turkestan General-Governorship (specifically the Transcaspian and Syr-Darya regions) between 1880 and 1906. Primary sources include administrative documents from the Russian State Historical Archive, materials from regional surveys published between 1890 and 1907, aggregate statistical data from the First General Census of the Russian Empire pertaining to the studied regions, and contemporary accounts. Our research concludes that during the 1880s and 1890s, the first mono-ethnic and mono-confessional German settlements were established in Turkestan. Key factors driving the migration of Germans from the Volga region included the imposition of military service on Mennonites and an agrarian crisis characterized by crop failures and famine. It is demonstrated that the Germans were able to create sustainable communities in their new locations, with natural population growth serving as the primary source of demographic increase until the onset of Stolypin’s agrarian reform.